2010
DOI: 10.4248/ijos10036
|View full text |Cite
|
Sign up to set email alerts
|

Applied Anatomic Site Study of Palatal Anchorage Implants Using Cone Beam Computed Tomography

Abstract: Aim The purpose of this study was to conduct quantitative research on bone height and bone mineral density of palatal implant sites for implantation, and to provide reference sites for safe and stable palatal implants.Methodology Three-dimensional reformatting images were reconstructed by cone beam computed tomography (CBCT) in 34 patients, aged 18 to 35 years, using EZ Implant software. Bone height was measured at 20 sites of interest on the palate. Bone mineral density was measured at the 10 sites with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…26 The anatomical structure of the palatal bone differs between individuals and between different areas within an individual. 22,27 The mean values and the ranges obtained at each one of the sites in the control group coincide with those of previously published series 18 we do not have references values for these measurements in individuals with DS. In the present study, PBT usually decreased progressively in a lateral direction from the midline and also in an anteroposterior direction, with exception of the area of the median palatal suture; these findings confirm the results of previous series in the general population.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…26 The anatomical structure of the palatal bone differs between individuals and between different areas within an individual. 22,27 The mean values and the ranges obtained at each one of the sites in the control group coincide with those of previously published series 18 we do not have references values for these measurements in individuals with DS. In the present study, PBT usually decreased progressively in a lateral direction from the midline and also in an anteroposterior direction, with exception of the area of the median palatal suture; these findings confirm the results of previous series in the general population.…”
Section: Discussionsupporting
confidence: 50%
“…11 This area has the obvious advantage that it does not contain anatomical structures such as blood vessels, nerves or tooth roots that could complicate insertion of the miniscrews 17 ; furthermore, the placement of TADs in this area does not interfere with tooth movements 14 and, compared with other sites, it offers greater comfort and better acceptance by patients. 12 The palatal bone has an irregular structure and morphology, 18 and it is therefore important to analyse the available bone before planning the insertion of miniscrews. Clinical examination, panoramic X-rays and cephalometry are of limited value in the assessment of PBT, 19 and it has been suggested that the best tool for determining PBT is the analysis of coronal CBCT images, 13 as image distortion and superposition is avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported on successful bone healing based on bone density information retrieved from CBCT-based data [13], but density values can be questioned due to distortion of Hounsfield Units (HU) in CBCT imaging, i.e., scanned regions of the same density in the skull can have different gray scale values in the reconstructed CBCT data set [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it provides good bony support [1,5-7]. Median and paramedian insertion as well as various mechanics have been described [4,8-13].…”
Section: Introductionmentioning
confidence: 99%